Measuring the effect of gender segregation on the gender gap in time-related underemployment - Juan Acosta-Ballesteros; María del Pilar Osorno-del Rosal; Olga María Rodríguez-Rodríguez (Journal for Labour Market Research, 2021)
This paper focuses on the impact that gender segregation in the labour market exerts on the underemployment gender gap for young adult workers in Spain. In order to analyse the relative importance of segregation in this gap, we develop a methodology based on two counterfactual simulations that provides a detailed decomposition of the gap into endowments and coefficients effects as well as the interaction of these effects. To the best of our knowledge, we are the first to perform a decomposition using bivariate probit models with sample selection. Using annual samples of the Spanish Labour Force Survey 2006-2016, the results show that working in female-dominated occupations or industries hinders working as many hours as desired, especially for women. Furthermore, we conclude that the gender gap in underemployment is mainly due to the different distribution of male and female workers across occupations and industries. Additionally, the different impact by gender that working in the same gender-typing jobs exerts on the risk of underemployment contributes to widening the gap.
Keywords: J16; J22; 330; Gender gap; Occupational and Industry segregation; Time-related underemployment; Counterfactual simulations; Decomposition analysis